Analysis of ZTE MRI application to sandstone and carbonate. Issue 2 (16th December 2020) - Covington, Kyle L.; Goroncy, Alexander K.; Lehmann, Teresa E.; Kou, Zuhao; Wang, Heng; Alvarado, Vladimir
Abstract: Microtomography (μCT) and nuclear magnetic resonance (NMR) have been used to characterize porous media for decades. Magnetic resonance imaging (MRI) enables direct visualization of pore architecture and many pulse sequences exist. In this work, we tested the MRI pulse sequence Zero Echo Time (ZTE) to study sandstone and carbonate for its ability to address short relaxation times. We aimed at resolving two fluid conduit scales, that is, pores and fractures. In this research, we study tighter porous systems than those previously reported using ZTE. Additionally, pore cluster analysis (PCA), combined with ZTE, can be used to analyze pore‐fracture connectivity of relatively large core plugs. We show that ZTE can resolve two‐scale pore systems simultaneously, that is, fractures and pores. By combining time‐domain NMR pore‐size analysis and PCA, we show that careful selection of resolution is necessary to understand transport in porous media.